1997
DOI: 10.1029/97eo00338
|View full text |Cite
|
Sign up to set email alerts
|

Expedition gathers new data on crust beneath Mexican West Coast

Abstract: During the spring of 1996, scientists explored the North American plate boundary of southern Mexico and the Gulf of California through the Crustal Offshore Research Transect by Extensive Seismic Profiling (CORTES‐P96) experiment (Figure la). Through dense sampling of the plates, the new data provides images that unravel the style of deformation along and across the subduction zone and in the Gulf interior, the dimensions of the accretionary prism, and the geometry of the subduction zone, which is well constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The strong sedimentation and shallow penetration did not allow imaging of magmatic products in other areas, except for some isolated submarine volcanoes. Lava bodies were interpreted from backscattering images, magnetic and seismic data for the upper Delfín basin and mainly along the Ballenas‐Salsipuedes channel [ Frías‐Camacho et al , 1999; Delgado‐Argote , 2000; Paz‐López et al , 2000; Paz‐López , 2000] using CORTES‐P96 cruise data [ Dañobeitia et al , 1997]. …”
Section: Introductionmentioning
confidence: 99%
“…The strong sedimentation and shallow penetration did not allow imaging of magmatic products in other areas, except for some isolated submarine volcanoes. Lava bodies were interpreted from backscattering images, magnetic and seismic data for the upper Delfín basin and mainly along the Ballenas‐Salsipuedes channel [ Frías‐Camacho et al , 1999; Delgado‐Argote , 2000; Paz‐López et al , 2000; Paz‐López , 2000] using CORTES‐P96 cruise data [ Dañobeitia et al , 1997]. …”
Section: Introductionmentioning
confidence: 99%
“…EISSLER and MCNALLY (1984) and SINGH et al (1985) suggested a dip angle of 20°for the interface between the Rivera and North American Plates. NÚ Ñ EZ-CORNÚ and SÁ NCHEZ-MORA (1999), reported a dip angle of 12°as estimated from local seismicity data, and similar values were obtained from reflection-refraction studies carried out in the central and northern regions of the Jalisco coast (DAÑ OBEITIA et al, 1997). More controversial are the geometry of the interface and the relative motion between the Rivera and Cocos Plates.…”
Section: Tectonic Settingmentioning
confidence: 52%
“…There is also considerable relief on the Rivera plate seaward of the trench. Seismic velocity models based on the OBS data indicate a dip of 8-128 for the subducting oceanic plate [6], consistent with the initial dip of the Benioff zone further landward [10]. The top of oceanic basement may be traced for about 10 km beneath the accretionary wedge, and the Rivera plate is covered by about 1 km of sediments as it enters the subduction zone.…”
Section: Tectonic Settingmentioning
confidence: 79%
“…Close to continental margins, determination of the depth to this reflector allows average geothermal gradients between the seabed and the BSR to be measured over wide areas [5]. Here we estimate conductive heat flow through sediments overlying young oceanic crust subducted beneath the western margin of Mexico at 208N, based on observations of a strong and continuous BSR in multichannel seismic reflection (MCS) profiles acquired during the Crustal Offshore Research Transect by Extensive Seismic Profiling (CORTES) experiment [6].…”
Section: Introductionmentioning
confidence: 99%